ANALISIS PEMBERIAN SANKSI DISIPLIN TERHADAP APARATUR SIPIL NEGARA: Analysis Of The Implementation Of Disciplinary Sanctions Against State Civil Apparatus - Danuarta Hatta Rabbani; Pamungkas, Yogo (Faculty of Law, Universitas Trisakti, 2025)
This research discusses the application of disciplinary sanctions against State Civil Servants (ASN) in Indonesia, especially Civil Servants (PNS). Based on Law Number 5 of 2014, ASN must comply with the principle of merit and carry out their duties professionally. However, disciplinary violations still occur, making sanction enforcement a challenge. The problems raised include: how Civil Servant (PNS) superiors enforce discipline, the effectiveness of sanctions, and the impact of disciplinary violations on ASN performance. This research is normative and descriptive. Secondary data were obtained through literature study and analyzed qualitatively. The results show that although disciplinary sanctions are regulated in Government Regulation Number 94 of 2021, many ASN do not feel their impact. In the case of Zaka Pringga Arbi, who received a demotion sanction, analysis shows the sanction was not proportional to the violation, indicating the need for fairer, more consistent enforcement. The conclusion emphasizes discipline as a key to ASN's success in government duties. Recommendations are needed to increase the effectiveness of disciplinary enforcement to strengthen ASN’s integrity and professionalism, thereby improving performance and public trust in government institutions.